Article RETRACTED due to malpractice Instability Burden Across Joints: A Patient-Reported Outcomes Measurement Information System (PROMIS)-Based Comparison of Hip Dysplasia, Knee, and Shoulder Instability - sen, Rimmi (Retos, 2026)
Purpose: The burden of joint instability on the patient’s general health has been well recognized in the shoulder and knee but not as much in the hip. This study compares patients who have undergone corrective surgery for instability of the hip knee, and shoulder to better understand their relative impact on quality of life. Methods: 230 instability correction procedures performed between 1-Jun-2018 and 31-Jan-2023 were included in the analysis: 62 dysplastic hips [Mean Age 31(16-47), BMI 25(18-33), ASA 2.0 (1-3) and 7 Males (11%)], 112 knees with ligamentous injuries [Mean Age 34(18-61), BMI 27(16-48), ASA 1.6(1-3) and 62 Males (55%)], and 56 unstable shoulders [Mean Age 38(18-67), BMI 27(20-37), ASA 2.0(1-3) and 39 Males (70%)]. Intra-operative surgical details including, arthroscopic treatment, as well as labral, cartilage, and bone corrections, were collected. Pre-operative and 1-year post-operative Physical and Mental PROMIS patient-reported outcome measures were also compiled. Results: In the hip group surgeries were: periacetabular osteotomy (PAO) (71%), PAO with scope (23%), and Arthroscopy alone (6%); in the shoulder group: 61% of patients received a scope, and 39% received open surgery; in the knee group: 85% of patients received ACL surgery alone while 15 received both ACL and Meniscus treatment. All patients improved their functional score with hip instability having the worst physical outcomes pre- and postoperatively. Mean Pre-operative Physical Health PROMIS score was [Hip 40.1 (SD 6.9); Knee 48.3 (SD 7.7); Shoulder 46.6 (SD 8.0)] and 12 months post-operative was [Hip 45.2 (SD 7.6); Knee 50.4 (SD 6.2); Shoulder 48.8 (SD 7.7)]. Conclusion: Joint instability carries a significant burden on patients’ both physical and mental quality of life. More importantly, instability from a bony deformity i.e. hip dysplasia is as impactful as soft tissue/ligamentous instability of the shoulder and knee. This analysis adds validity to instability as the leading pathomechanism of hip dysplasia.